PERLUKAH GENDER DIPERMASALAHKAN? (Al'Adalah, 2002)
Gender is something different from sex. Sex refers to biological anatomy of human that distinguish between man and woman, it is unchangeable. Whereas gender refers to social construction on what and how men or women should be, behave, act, etc. Surely, social construction is different from one region to another, it is changeable. It depends on social expectation in one area. In fact, it is often gender-biased from which women often suffer. That is why gender should be questioned and we need to deconstruct the gender-based social construction.